Symposium 5: Perceptions of guest lecturers’ impact on online learning communities - Costello, Jane (Proceedings of the International Conference on Networked Learning, 2012)
A phenomenographic approach to case study is presented as a proposed methodology to researching guest speakers’ impact in networked learning communities. This work-in-progress paper outlines the proposed use of case study and phenomenography in exploring learners’ experience of guest speakers’ impact on students’ in online learning communities in higher education (HE). The rationale for this chosen methodology is outlined, as well as its epistemological and ontological underpinnings. The inclusion of guest speakers in higher education courses, such that they share experience with and learn with students and instructors through synchronous or asynchronous communication, is an area little studied to date. Little is known about guest speakers’ impact on learning beyond a few documented benefits afforded by guest speakers in face-to-face learning environments. For example, guest speakers bridge theory and practice (praxis) through experiences they share with the class. Data collected from semi-structured interviews in each case will be formulated into outcome spaces. This multiple case study will generate outcomes spaces that depict the categories of description as provided by participants. Following Åkerlind’s (2008) method of focusing on student experience, the outcome space will be representative of participants’ variation of experience, from students’ perspectives. The project’s issues and challenges, as understood to-date, are outlined. Proposed next steps are identified. This paper presents an alternate approach to the use of phenomenography in researching learning in a student-centred phenomenographic approach to case study.